Association of transmural dispersion of ventricular repolarization (Tpeak-Tend interval) with components of metabolic syndrome: data from the ESSE-RF3 - E. V. Garbuzova; A. A. Kuznetsov; A. M. Nesterets; A. D. Khudyakova; V. S. Shramko; A. E. Imaeva; G. A. Muromtseva; Yu. A. Balanova; G. I. Simonova (Кардиоваскулярная терапия и профилактика)
Aim. To study the associations of the Tpeak-Tend interval (TpTe) with components of metabolic syndrome (MS) in a sample of Novosibirsk residents.Material and methods. The study included 1042 residents of Novosibirsk (510 (48,9%) men) aged 35-74 years. The examination included the collection of demographic and social data, anthropometry, blood pressure (BP) measurement, and electrocardiography (ECG). MS was determined according to the 2013 criteria. The TpTe interval from the peak, as the maximum positive or negative T wave deviation, to the end of the T wave, was measured manually in lead V5. The corrected TpTe (cTpTe) interval was used in the study.Results. The cTpTe is inversely associated with female sex (B 3,390, 95% confidence interval (CI): (-5,516-2,504), p=0,001). The cTpTe interval is associated with a blood pressure (BP) ≥140/90 mm Hg (B 3,154, 95% CI: (1,614-4,688), p=0,001), low-density lipoprotein cholesterol (LDL-C) >3,0 mmol/l (B 1,818, 95% CI: (0,409-3,544), p=0,030), regardless of other MS components, sex and age. The cTpTe interval was higher in individuals with BP ≥140/90 mm Hg compared with individuals with BP <140/90 mm Hg (69,08 95% CI: 67,59-70,66 vs 65,93 95% CI: 64,60-67,24; p=0,001), and in persons with LDL-C >3,0 mmol/l (68,41 95% CI: 67,11-69,63 vs 66,60 95% CI: 65,02-68,23; p=0,023), compared with individuals with LDL-C <3,0 mmol/l.Conclusion. The cTpTe interval, considered as an indicator of transmural dispersion of ventricular repolarization, is shorter in women than in men and is associated with hypertension and atherogenic dyslipidemia, regardless of other MS components.